Mitophagy: a balance regulator of NLRP3 inflammasome activation - Kim, Min-Ji (BMB Rep, 2016)
The NLRP3 inflammasome is activated by a variety of external or host-derived stimuli and its activation initiates an inflammatory response through caspase-1 activation, resulting in inflammatory cytokine IL-1β maturation and secretion. The NLRP3 inflammasome activation is a kind of innate immune response, most likely mediated by myeloid cells acting as a host defense mechanism. However, if this activation is not properly regulated, excessive inflammation induced by overactivated NLRP3 inflammasome can be detrimental to the host, causing tissue damage and organ dysfunction, eventually causing several diseases. Previous studies have suggested that mitochondrial damage may be a cause of NLRP3 inflammasome activation and autophagy, which is a conserved self-degradation process that negatively regulates NLRP3 inflammasome activation. Recently, mitochondria-selective autophagy, termed mitophagy, has emerged as a central player for maintaining mitochondrial homeostasis through the elimination of damaged mitochondria, leading to the prevention of hyperinflammation triggered by NLRP3 inflammasome activation. In this review, we will first focus on the molecular mechanisms of NLRP3 inflammasome activation and NLRP3 inflammasome-related diseases. We will then discuss autophagy, especially mitophagy, as a negative regulator of NLPP3 inflammasome activation by examining recent advances in research. [BMB Reports 2016; 49(10): 529-535]